The flexible economy : causes and consequences of the adaptability of national economies - Killick, Tony (Routledge, 1995)
The accelerating pace of global change demands that economies must be adaptable. Economies which are flexible flourish, as in Eastern Asia. Inflexible economies stagnate, as in Eastern Europe and Africa. However even though adaptability governs the long-term progress of economies, economists have had little to say about the nature and determinants of economic flexibility. This book redresses that situation. A prestigious team of contributors address the key theoretical and empirical issues, using a wide range of country studies.